Processing of layered porous mullite ceramics - Kalemtaş, Ayşe; Ozey, Nigar; Aydin, Meryem Turkay Aytekin (Springer, 2018)
In the current study, layered porous mullite ceramics with different pore sizes were produced via polymeric sponge method by using CC31 commercial-grade kaolin as starting raw material. Polyurethane sponges with three different pore sizes (10, 20, and 30 ppi) changing from coarse to fine pores were physically assembled and then prepared ceramic slurry was impregnated into this structure to achieve the designed layered porous structure. After drying the polymeric sponges impregnated with the slurry, binder burnout and sintering studies were carried out. Phase composition and microstructure evolution of the porous samples, sintered at 1300 degrees-1600 degrees C for 1 and 3 h dwell time at a 3 degrees C/minute constant heating rate, were investigated. In situ mullite phase formation was achieved at all sintering conditions. It was determined that mullite grain morphology development strongly depends on the sintering temperature and time. Sintering at 1300 degrees C for 1 h resulted in the formation of equiaxed mullite grains. When the sintering temperature was increased to 1400 degrees C, first elongated fine mullite grains were achieved. Increasing dwell time at this temperature from 1 to 3 h resulted in more elongated mullite grain development. It was observed that aspect ratio of the mullite grains was significantly increased when the sintering temperature was increased to 1500 and 1600 degrees C. Scanning electron microscopy investigations demonstrated that the mullite needles do not reveal a significant preferred orientation and all porous mullite samples have uniform microstructure. It was determined that highly porous (60-70%) and light weight (0.7-1.1 g cm(-3)) layered mullite ceramics were fabricated.
Keywords: Porous ceramics; Layered design; Polymeric sponge method; Mullite